Aluminum‐Catalyzed One‐Pot Synthesis of Polyester‐b‐Polypeptide Block Copolymers by Ring‐Opening Polymerization. Issue 14 (26th March 2019) - Schmid, Thibault E.; Robert, Carine; Richard, Vincent; Raman, Sumesh K.; Guérineau, Vincent; Thomas, Christophe M.
Abstract: Polypeptides are a class of important biomaterials that are extensively utilized in applications such as drug delivery systems, sensors, tissue engineering, biomimetic synthesis of ordered inorganic nanostructures, and catalysis. In particular, the association of polypeptides to polyesters in copolymer architectures provides versatile original materials. However, the catalytic formation of this type of peptide‐based copolymers remains a considerable synthetic challenge. Here, a new strategy to obtain copolymer materials by one‐pot catalysis is reported, which confers great interest to the approach. Abstract : The sequential ring‐opening polymerization of α‐aminoacid‐ N ‐carboxyanhydride and lactide monomers using a commercially available salen aluminum complex as initiator proceeds readily at room temperature to give the corresponding polypeptide‐polylactide block copolymers.